Inter-specific hybridization of Alnus rubra and Alnus rhombifolia: preliminary report of a new taxon and DNA marker resources for bioenergy feedstock production - Brian J. Stanton; Teodora Best; Nurul Islam-Faridi; Carlos Gantz; Kathy Haiby; Lianna J. Johnson; Rich Shuren; Alex Stanish; Margaret Staton; T. Casey Weathers; Di Wu; John E. Carlson (Tree Genetics & Genomes, 2020)

Lifeform indicators reveal large‐scale shifts in plankton across the North‐West European shelf - Jacob Bedford; Clare Ostle; David G. Johns; Angus Atkinson; Mike Best; Eileen Bresnan; Margarita Machairopoulou; Carolyn A. Graves; Michelle Devlin; Alex Milligan; Sophie Pitois; Adam Mellor; et al. (Global Change Biology, 2020)
Increasing direct human pressures on the marine environment, coupled with climate‐driven changes, is a concern to marine ecosystems globally. This requires the development and monitoring of ecosystem indicators for effective management and adaptation planning. Plankton lifeforms (broad functional groups) are sensitive indicators of marine environmental change and can provide a simplified view of plankton biodiversity, building an understanding of change in lower trophic levels. Here, we visualize regional‐scale multi‐decadal trends in six key plankton lifeforms as well as their correlative relationships with sea surface temperature (SST). For the first time, we collate trends across multiple disparate surveys, comparing the spatially and temporally extensive Continuous Plankton Recorder (CPR) survey (offshore) with multiple long‐term fixed station‐based time‐series (inshore) from around the UK coastline. These analyses of plankton lifeforms showed profound long‐term changes, which were coherent across large spatial scales. For example, ‘diatom’ and ‘meroplankton’ lifeforms showed strong alignment between surveys and coherent regional‐scale trends, with the 1998–2017 decadal average abundance of meroplankton being 2.3 times that of 1958–1967 for CPR samples in the North Sea. This major, shelf‐wide increase in meroplankton correlated with increasing SSTs, and contrasted with a general decrease in holoplankton (dominated by small copepods), indicating a changing balance of benthic and pelagic fauna. Likewise, inshore‐offshore gradients in dinoflagellate trends, with contemporary increases inshore contrasting with multi‐decadal decreases offshore (approx. 75% lower decadal mean abundance), urgently require the identification of causal mechanisms. Our lifeform approach allows the collation of many different data types and time‐series across the NW European shelf, providing a crucial evidence base for informing ecosystem‐based management, and the development of regional adaptation plans.

Utilizing Eutrophication Assessment Directives From Transitional to Marine Systems in the Thames Estuary and Liverpool Bay, UK - Naomi Greenwood; Michelle J. Devlin; Mike Best; Lenka Fronkova; Carolyn A. Graves; Alex Milligan; Jon Barry; Sonja M. van Leeuwen (Frontiers in Marine Science, 2019)

Higher resources decrease fluctuating selection during host–parasite coevolution - Laura Lopez Pascua; Alex R. Hall; Alex Best; Andrew D. Morgan; Mike Boots; Angus Buckling (Ecology Letters, 2014)
We still know very little about how the environment influences coevolutionary dynamics. Here, we investigated both theoretically and empirically how nutrient availability affects the relative extent of escalation of resistance and infectivity (arms race dynamic; ARD ) and fluctuating selection (fluctuating selection dynamic; FSD ) in experimentally coevolving populations of bacteria and viruses. By comparing interactions between clones of bacteria and viruses both within‐ and between‐time points, we show that increasing nutrient availability resulted in coevolution shifting from FSD , with fluctuations in average infectivity and resistance ranges over time, to ARD . Our model shows that range fluctuations with lower nutrient availability can be explained both by elevated costs of resistance (a direct effect of nutrient availability), and reduced benefits of resistance when population sizes of hosts and parasites are lower (an indirect effect). Nutrient availability can therefore predictably and generally affect qualitative coevolutionary dynamics by both direct and indirect (mediated through ecological feedbacks) effects on costs of resistance.

The importance of who infects whom: the evolution of diversity in host resistance to infectious disease - Mike Boots; Andy White; Alex Best; Roger Bowers (Ecology Letters, 2012)
Variation for resistance to infectious disease is ubiquitous and critical to host and parasite evolution and to disease impact, spread and control. However, the processes that generate and maintain this diversity are not understood. We examine how ecological feedbacks generate diversity in host defence focussing on when polymorphism can evolve without co‐evolution of the parasite. Our key result is that when there is heritable variation in hosts in both their transmissibility and susceptibility along with costs to resistance, there is the possibility of the evolution of polymorphism. We argue that a wide range of behavioural or physiological mechanisms may lead to relationships between transmissibility and susceptibility that generate diversity. We illustrate this by showing that a tendency for higher contacts between related individuals leads to polymorphism. Only dimorphisms can evolve when infection is determined only by an individuals' susceptibility or when transmissibility and susceptibility are simply positively or negatively correlated.

Local transmission processes and disease-driven host extinctions - Alex Best; Steve Webb; Janis Antonovics; Mike Boots (Theoretical Ecology, 2012)